Cytotoxicity of Kembang Bulan (Tithonia diversifolia ) Ethanolic Leaf Extract on Rabbit Limbal Mesenchymal Stem Cells - Plumeriastuti, Hani; Zahro, Vida Seanita; Triakoso, Nusdianto; Rantam, Fedik Abdul; Hamid, Iwan Sahrial; Effendi, Mustofa Helmi; Proboningrat, Annise (Media Kedokteran Hewan, 2022)
Kembang Bulan (Tithonia diversifolia ) is known as an herbal plant that has many useful properties to cure disease, such as diabetes, malaria, and other infections. Instead of much usefulness, T. diversifolia has main biological properties that may induce toxicity in this plant known as sesquiterpene lactones. The aim of this study was to identify the cytotoxicity effect of T. diversifolia leaf extract on limbal mesenchymal stem cells of rabbits using the MTT assay. T. diversifolia leaf extract was divided into 4 concentrations (0.5%, 0.25%, 0.125%, and 0.0625%) and given to limbal mesenchymal stem cells of rabbits in 96-well microplates, which would be incubated for 24 hours. The cytotoxicity result was obtained using the MTT assay method. Every well would be observed to see the cell life level of each concentration. The optical density absorbance was calculated using a microplate reader. T. diversifolia leaf extract with a concentration of 0.0625% has the biggest viability with a level of existence of limbal mesenchymal stem cells of 50%, and the other T. diversifolia leaf extract concentrations of 0.5%, 0.25%, and 0.125% have less than 50% level of existence of limbal mesenchymal stem cells.